IMPLEMENTATION OF MODERATE LEADERSHIP IN EDUCATIONAL INSTITUTIONS IN CENTRAL LOMBOK - Edi Supardi Moh, Iwan Fitriani (STAI Syaichona Moh. Cholil Bangkalan, 2024)
Moderate leadership is leadership that can be used to reconcile differences. The implementation of moderate leadership is the central point and policy determinant of activities to be implemented in the school environment. Moderate leadership aims to provide understanding to all teachers to work well, have high performance standards and in religious activities still uphold religious beliefs. This research uses a qualitative approach. Data was collected by in-depth interviews with informants. Researchers are the main key instrument in data collection. The data was analyzed using the stages of data presentation, data condensation and drawing conclusions. Checking the validity of the data is carried out by triangulation until the data is saturated. The research results show that the implementation of moderate leadership has been carried out well, with activities including: curriculum development, teacher training, student involvement, classroom environment